Some features of the formation of mathematical representations in preschoolers in the process of familiarizing them with the size and shape of objects and the concepts of quantities and numbers (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article discusses some issues of the methodology for the formation of sizes and sizes of objects in preschoolers. Emphasizing that children learn the sizes of objects mainly in sensory ways in the process of examination, comparison and comparison, grouping, and the sizes - by measuring objects and using numbers for the purpose of quantitative assessment, the sequence of mastering the values at preschool age, ways of mastering preschool children measurement of quantities, as well as methodological requirements for teaching children five years of measurement activity. This article examines some of the methodological aspects of the formation of the concept of number and magnitude in preschoolers